2000
DOI: 10.1302/0301-620x.82b3.0820336
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of fractures of the shaft of the humerus by dynamic compression plate or intramedullary nail

Abstract: We randomised prospectively 44 patients with fractures of the shaft of the humerus to open reduction and internal fixation by either an intramedullary nail (IMN) or a dynamic compression plate (DCP). Patients were followed up for a minimum of six months. There were no significant differences in the function of the shoulder and elbow, as determined by the American Shoulder and Elbow Surgeons' score, the visual analogue pain score, range of movement, or the time taken to return to normal activity. There was a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
169
2
17

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(199 citation statements)
references
References 17 publications
11
169
2
17
Order By: Relevance
“…Both, ORIF and IN are well-established procedures with high rates of 85-93 % of recovery following primary radial nerve palsy [12,[17][18][19][20][21]. In the case of acute primary radial nerve palsy open reduction facilitates fracture treatment and enables simultaneous exploration of the radial nerve to determine the extent and the type of lesion [1,7,18].…”
Section: Discussionmentioning
confidence: 99%
“…Both, ORIF and IN are well-established procedures with high rates of 85-93 % of recovery following primary radial nerve palsy [12,[17][18][19][20][21]. In the case of acute primary radial nerve palsy open reduction facilitates fracture treatment and enables simultaneous exploration of the radial nerve to determine the extent and the type of lesion [1,7,18].…”
Section: Discussionmentioning
confidence: 99%
“…While there are several methods of operative intervention for humerus shaft fractures, the internal fixation methods can be broadly grouped as plating or intramedullary techniques. Interlocking nailing is preferable in communited, segmental and pathological fractures while plating may be the preferred option where radial nerve exploration is contemplated [5,13,14]. Conventional plating techniques involve an extensive surgical approach for open reduction of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with mentioned studies, our technique can significantly reduce the operating time of nail insertion in patients with humeral shaft fractures (P<0.05). McCormack et al [17] compares the outcomes of humeral shaft fractures via intra-medullary nailing and dynamic compression plate, and the rate of non-union in the nailing group was 9.5 %. Also, Singisetti and Ambedkar [4] in a prospective study compared the clinical results of nailing and plating, and the non-union rate of the nailing group was 5 %.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the above studies, our technique leads to slightly increased non-union rate. McCormack et al [17] reported three cases of post-operative radial nerve palsy among 21 patients who underwent intra-medullary nailing (14.2 %). In our patients, only one case of post-operative radial nerve palsy was detected, and the patient recovered after about 6 weeks of operation.…”
Section: Discussionmentioning
confidence: 99%